RECONFIGURATION OF LIVING HADITH IN THE DIGITAL SPACE: BETWEEN AUTHENTICITY OF TRANSMISSION AND POPULARIZATION OF ISLAMIC EDUCATION CONTENT ON SOCIAL MEDIA - Muhammad Sabari; Willy Pauzan Alfi; M. Suparta; Romlah Abubakar Askar (JOURNAL OF QUR'AN AND HADITH STUDIES, 2026)
The rapid expansion of social media has transformed how ḥadīth-based Islamic educational content is produced, transmitted, and consumed. This study examines the reconfiguration of living ḥadīth in digital spaces, focusing on the tension between classical ḥadīth transmission authenticity and social media popularization demands. Employing a qualitative design integrating Critical Discourse Analysis (CDA) of content on Instagram, TikTok, and YouTube with phenomenological interviews of 12 content creators and 15 audience participants, the study identifies three dominant discursive patterns: textual-visual repackaging, narrative embodiment, and scholarly mediation. Findings reveal a structural ‘authenticity-popularity paradox’ wherein platform algorithmic logic systematically disadvantages the scholarly apparatus of classical ḥadīth transmission. A Reconstructive Living Ḥadīth Model for Digital Spaces (RLHM-DS) is proposed as a normative-qualitative framework operating across three levels, i.e.,  Production, Platform, and Reception, for improving ḥadīth transmission quality in Islamic digital education. The study contributes an integrated application of Fairclough’s CDA with classical isnād-based authenticity standards and living ḥadīth theory within the Indonesian Islamic education context, addressing a gap in the existing literature that has yet to systematically combine these analytical traditions.